Smartphone photography training for students of MA Aisyiyah Sungguminasa Gowa: Creating engaging visual content - Syarif, Ahmad; Riyadi, Ilham; Manggaga, Indah Pratiwi; Lukman, Lukman; Zain, Luthfiah; Harun, Muhammad Hidayat Hesa (Community Empowerment, 2025)
This practical training on smartphone photography was conducted at Madrasah Aliyah Aisyiyah Sungguminasa, Gowa, with the aim of equipping students with the skills to create compelling visual content. Initially, many students lacked familiarity with fundamental photography techniques using their smartphones. The training curriculum was designed to introduce basic principles, including lighting, composition, camera angles, visual storytelling, and photo editing using mobile applications. The outcomes of this activity demonstrated a significant improvement in students' knowledge and skills. Post-training, 85% of the participants showed a solid understanding of photography fundamentals, 90% were able to capture high-quality photographs, and 88% successfully shared their photos on social media in a constructive manner. This initiative is expected to be continued to further nurture students' creativity and confidence in producing meaningful and impactful content.